Review of the genera Rondoniella Kaszab, 1970 and Durandius Kaszab, 1970 (Coleoptera: Tenebrionidae), with description of R. hosoishii sp. nov. from an ant nest in Cambodia - Maruyama, Munetoshi; Ando, Kiyoshi (Zootaxa, 2022)
The enigmatic tenebrionid genera Rondoniella Kaszab, 1970 and Durandius Kaszab, 1970 are briefly reviewed and diagnosed. Rondoniella hosoishii sp. nov. is described based on specimens collected from a nest of the arboreal ant Crematogaster sewardi in Cambodia. Because of where R. hosoishii sp. nov. was collected and its specialized morphology, the members of Rondoniella and its close relative Durandius are considered to be myrmecophilous, as was suggested in the original description. They also have reduced mouthparts, which are unknown in other tenebrionids, and they might receive food from ants by trophallaxis.